NEED ANALYSIS OF TEACHING AND LEARNING MARITIME ENGLISH IN NAUTICAL CLASS OF STIMART “AMNI” SEMARANG - Ever Nicolas; Endah Fauziningrum (Edulingua: Jurnal Linguistiks Terapan dan Pendidikan Bahasa Inggris, 2018)
International Maritime Organization (IMO) clearly requires adequate communication skills in the English language for Maritime Academy level. Often the resources allocated for teaching english are minimal and the acquisition of speaking and writing skills are subordinated to the acquisition of technical maritime expertise. The aims of this paper is to find out the problems faced by nautical cadets of  STIMART “AMNI” Semarang in Maritime English class and to investigates the needs of the Nautical cadets in order to develop good syllabus and appropriate to their need. The present research finds that the language abilities that the maritime cadets mostly need are speaking, listening and writing skills. This paper also explain some current problems that faced by cadets toward Martime English course. They should be communicate well to the other crew when they do their apprentice on board of a ship. The findings are unequivocal signals for language educators to adapt new approaches to teaching English for specific purposes that suitable for the cadets.